1987
DOI: 10.1002/mrc.1260250306
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins as chiral complexing agents in water, and their application to optical purity measurements

Abstract: The interaction of p-cyclodextrin with propanolol hydrochloride was shown by NMR to produce diastereomeric pairs observable in D,O solution at 400 MHz. By addition of racemate to pure ( -)-isomer, the usefulness of this novel technique in being able to measure optical purity in water down to the 1% level was demonstrated. Using changes in chemical shifts and NOE effects, a possible structure for the inclusion complex is proposed. y-Cyclodextrin induced larger shifts in the spectrum than the p-equivalent, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(42 citation statements)
references
References 8 publications
2
37
0
1
Order By: Relevance
“…Deuterated NMR solvents were obtained from Aldrich Chemical and used as received. Europium(III) and praseodymium(III) complexes of 6,6,7,7,8,8,8heptaÑuorooctane-3,5-dione (fod),23 the silver complex of fod,24 Crown 116 and Crown 217 were prepared, puriÐed and characterized according to published procedures. All solvents used in the synthetic preparations were dried by established procedures prior to use.…”
Section: Reagentsmentioning
confidence: 99%
“…Deuterated NMR solvents were obtained from Aldrich Chemical and used as received. Europium(III) and praseodymium(III) complexes of 6,6,7,7,8,8,8heptaÑuorooctane-3,5-dione (fod),23 the silver complex of fod,24 Crown 116 and Crown 217 were prepared, puriÐed and characterized according to published procedures. All solvents used in the synthetic preparations were dried by established procedures prior to use.…”
Section: Reagentsmentioning
confidence: 99%
“…The interior of the cavity is often hydrophobic, such that the hydrophobic portion of organic salts is stabilized by insertion into the cavity in water. Native cyclodextrins, [14][15][16][17][18] trimethyl-b-cyclodextrin, [19][20][21][22][23] and carboxymethylated cyclodextrins [24][25][26][27][28][29] are one family of water-soluble cavity compounds. The crown ether (18-crown-6)-2,3,11,12-tetracarboxylic acid has been used in water as a chiral solvating agent for primary amines, 30 although the enantiomeric discrimination with this crown ether is better in methanol and acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Greatbanks & Pickford (Greatbanks & Pickford, 1987) concluded that when  H3 >  H5, occurs partial inclusion of the guest inside the cavity and when  H3 <  H5, a total inclusion takes place.…”
Section: H-nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%